2008 IEEE Radar Conference 2008
DOI: 10.1109/radar.2008.4720949
|View full text |Cite
|
Sign up to set email alerts
|

Area and power efficient mismatched filters based on sidelobe inversion

Abstract: A computationally efficient mismatched filter comprised of a matched filter in cascade with a multi-stage filter based on sidelobe inversion is proposed. For this approach to work, the autocorrelation of the given code has to satisfy certain conditions that are derived in this work. If in addition, the sidelobes are sparse and of small integer values, such as in Barker codes and Huffman sequences, then the proposed filters are shown to be computationally very efficient. When implemented in VLSI, they require s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…One of the widely used approaches to suppress the ACF sidelobes of a waveform/code is via windowing whereby the peak sidelobe level is reduced, but at the cost of increasing the mainlobe width. Mismatched filters like the ones introduced in [5][6][7][8] could also be used to reduce ACF sidelobes at the cost of a small loss in signal-to-noise ratio. In [9], it is shown that complete sidelobe cancellation for a class of aperiodic codes is possible using additive-multiplicative processing of the matched filter (MF) output.…”
Section: ๐‘…[๐‘›]mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the widely used approaches to suppress the ACF sidelobes of a waveform/code is via windowing whereby the peak sidelobe level is reduced, but at the cost of increasing the mainlobe width. Mismatched filters like the ones introduced in [5][6][7][8] could also be used to reduce ACF sidelobes at the cost of a small loss in signal-to-noise ratio. In [9], it is shown that complete sidelobe cancellation for a class of aperiodic codes is possible using additive-multiplicative processing of the matched filter (MF) output.…”
Section: ๐‘…[๐‘›]mentioning
confidence: 99%
“…Mismatched filters like the ones introduced in [5][6][7][8] could also be used to reduce ACF sidelobes at the cost of a small loss in signal-to-noise ratio. In [9], it is shown that complete sidelobe cancellation for a class of aperiodic codes is possible using additive-multiplicative processing of the matched filter (MF) output.…”
Section: Introductionmentioning
confidence: 99%